Association between serum vitamin B12 levels and metabolic syndrome in a euthyroid population - Guarnizo-Poma, Mirella (2018)
Aims: To determine the association between serum levels of vitamin B12 and metabolic syndrome (MetS) in a population of euthyroid adults. Materials and methods: We carried out an analytical cross-sectional study in euthyroid adults of both sexes, who attended the outpatient service of a private clinic in Lima-Peru during the 2012–2016 period. Participants were divided into tertiles (low, intermediate and high) according to their serum vitamin B12 values. MetS was defined when three or more metabolic criteria were met by the participants. We elaborated crude and adjusted Poisson regression models to evaluate the association between the serum vitamin B12 tertiles and the presence of MetS. The reported association measure was the prevalence ratio (PR) with their respective 95% confidence intervals (95%CI).